ESCOLHA ADEQUADA DOS TESTES ESTATÃSTICOS PARA COMPARAÃ‡Ã•ES MÃšLTIPLAS - Conagin, Armando; Gomes, F. Pimentel (REVISTA DE AGRICULTURA, 2015)
ESCOLHA ADEQUADA DOS TESTES ESTATÃSTICOS PARA COMPARAÃ‡Ã•ES MÃšLTIPLAS